Analisis Strategi Fasilitasi Alat Peraga Kampanye di Masa Pandemi Covid-19 Pada Pemilihan Kepala Daerah - Muhammad Yahya; Hamdani Harahap; Arifin Saleh (PERSPEKTIF, 2022)
The purpose of this research is to find out and analyze the dynamics of the implementation of the Facilitation of Campaign Props (APK), the inhibiting factors and the implementation of facilitation in the Covid-19 Pandemic Period in the Election of Regents and their representatives in the Regency. Sergai Year 2020. Based on the description of the problem, the researcher chose to use a qualitative approach that is exploratory and inductive, the postpositivism paradigm with descriptive research type because it clarifies or explores phenomena or facts of social phenomena. The results showed that the implementation of APK facilitation in the 2020 Sergai Regent and Deputy Elections went in an orderly and peaceful manner despite the delay in submitting the APK to the Trendy Faithful Paslon. This is due to the dynamics and the nomination dispute where the KPU cannot print the APK if the Paslon has not been determined. The inhibiting factors in APK facilitation are (a) the lack of response from the Paslon in submitting the APK design and materials on time (b) the auction process (if any) and human resources who lack control over the procurement of government goods and services (c) corruption in the 2020 election grant budget corruption. Regency. Sergai has executed a good strategy in APK facilitation.